Delight Bakery / Adha Sarbini and Azman Md Nor - Sarbini, Adha; Md Nor, Azman (Faculty of Applied Sciences, 2005)
Delight Bakery will be located at Lot 32, Jalan Tengku Ampuan Zabedah K9/K, Section 9, 40100 Shah Alam, Selangor Darul Ehsan. Delight Bakery provides up to a few varieties of products. We serve many types of cake and bread. Our business will be serving style. We are offering any delivery services in the intention to make our customers feel the nice products.